Need Analysis of Primary School Promotion Media - Rumsant, Fayra Adzanie; Helmanto, Fachri; Ichsan, Muhammad (Mitra Palupi, 2024)
Background: In an increasingly competitive world of education, the importance of school promotion is increasingly felt. Schools must be able to compete to attract prospective students and parents. Purpose: This research aims to determine the needs of schools in carrying out promotions. Design and methods: This study used qualitative research methods. Needs analysis is based on the Hutchinson & Waters model which focuses on aspects necessities, lacks, and wants. Interviews were conducted with four PPDB administrators including teachers, PPDB Chair, and School Administrative Staff. The analysis technique used is thematic analysis, while validation is carried out using member checking. Results: The results of the study show that schools need promotions in printed form. With this, schools can achieve their promotional goals in a more widespread and efficient manner.